Predicting Regional Variations in Nationalism With Online Expression of Disgust in China - Gao, Shuqing; Chen, Hao; Lai, Kaisheng; Qian, Weining (Frontiers in Psychology, 2021)
Disgust is one of the basic emotions and is part of the behavioral immune system, which evolutionarily protects humans from toxic substances as well as from contamination threats by outgroup members. Previous works reveal that disgust not only activates humans’ defense against potential individual and collective threats, but also leads to severe moral judgments, negative intergroup attitudes, and even conservative political orientations. As is already known, nationalism is an ideology that features both negative feelings toward outgroups and beliefs about native superiority or privileges. Evidence from previous studies suggests that disgust is related to nationalism’s several components but lacks direct research on nationalism and disgust. The current study examines the relationship between disgust and nationalism in China at both individual and regional levels. In study 1, participants temporally induced disgust (vs. control) increasing the adoption of nationalism. In Study 2, we analyzed covariation in disgust expression in the Chinese micro-blog Weibo and the nationalism index as part of an online large-scale political survey http://zuobiao.me/ at the province level across Mainland China. The results show that online expression of disgust positively predicts nationalistic orientation at the regional level. Finally, we discuss how the findings shed light on research concerning online emotion expression and potential future directions.